White Fang [videorecording (DVD)] - Kleiser, Randal; Brandauer, Klaus Maria; Hawke, Ethan, 1970-; Cassel, Seymour, 1935-2019-; London, Jack, 1876-1916 (Disney DVD : Distributed by Buena Vista Home Entertainment, 2002)
Story of a young man who hopes to strike it rich in the Yukon gold country at the turn of the century and his relationship with the wolf-dog White Fang.